Injection ferrite magnetic powder, preparation method, injection ferrite material and application

By doping La-Co ion and controlling the flux ratio, injected ferrite magnetic powder with excellent magnetic properties and good fluidity was prepared, which solved the problem of insufficient magnetic properties and fluidity of injected ferrite materials in the prior art.

CN119462121AActive Publication Date: 2025-02-18HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411650796.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

It is difficult for existing injected ferrite materials to have coarse particle size, good particle morphology and excellent magnetic properties at the same time, resulting in insufficient fluidity and magnetic properties.

Method used

Through La-Co ion doping and controlling the ratio of H3BO3 to SrCl2, Sr1-x-yLaxCayFe12-zCozO19 injection ferrite magnetic powder was prepared to ensure that its average aspect ratio L/D is within the range of 1.2 to 3.0, and appropriate combination ball milling, vibration milling and heat treatment improve their fluidity and magnetic properties.

Benefits of technology

The injection of ferrite magnetic powder has excellent flowability and excellent magnetic properties, and is suitable for the preparation of high-performance magnetic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140867520000141
    Figure BDA0005140867520000141
  • Figure BDA0005140867520000151
    Figure BDA0005140867520000151
Patent Text Reader

Abstract

The invention provides injection ferrite magnetic powder, a preparation method, an injection ferrite material and application, the chemical formula of the injection ferrite magnetic powder is Sr < 1-x-y > LaxCayFe < 12-z > CozO19, the D50 size is 1.5-2.5 [mu] m, and the average length-diameter ratio L / D is 1.2-3.0; wherein 0 lt; x is less than or equal to 0.4, 0lt; y is less than or equal to 0.4, 0lt; z < = 0.25, 1.3 < = x / z < = 1.6. The injection ferrite magnetic powder provided by the invention not only has relatively large particle size, but also has good particle morphology due to the average length-diameter ratio L / D of 1.2-3.0, so that the injection ferrite magnetic powder has relatively excellent flowability; in addition, due to doping of La and Co, the injection ferrite magnetic powder also has excellent magnetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field and relates to an injected ferrite magnetic powder, in particular to an injected ferrite magnetic powder and a preparation method, an injected ferrite material and an application. Background Art

[0002] Ferrite permanent magnet materials are widely used in motors, magnetic storage, magnetic adsorption and magnetic sensing due to their rich raw materials, simple preparation process, high temperature resistance, corrosion resistance and low material cost. They are currently the largest type of permanent magnet materials. Ferrite permanent magnet materials can be divided into two categories according to the preparation process: sintered ferrite and bonded ferrite. Among them, injection ferrite materials are a type of bonded ferrite material formed by filling ferrite magnetic powder in an engineering plastic matrix. This material can be made into various complex shaped magnetic devices by injection molding, and can also be integrally injection molded with other inserts. Compared with sintered ferrite, injection ferrite has the advantages of high one-time molding dimensional accuracy, superior mechanical properties and large morphological freedom. Therefore, it is widely used in many micro motors and precision magnetic sensor devices. The disadvantage of injection ferrite magnets is that the magnetic properties are relatively low, and the magnetic energy product is generally below 2.3MGOe. In recent years, as magnetic devices are increasingly miniaturized and lightweight, the market has put forward higher requirements on the magnetic properties of magnetic materials. Therefore, how to prepare high-performance injected ferrite materials is a hot topic in the research field of magnetic materials.

[0003] Since the injection ferrite material is a composite material composed of ferrite magnetic powder and engineering plastic binder, the key to improving the injection ferrite material is to prepare high-performance ferrite magnetic powder. Generally speaking, the magnetic powder suitable for preparing high-performance injection ferrite permanent magnet materials should meet the following conditions: (1) It has excellent magnetic properties, that is, high remanence, high coercive force and high magnetic energy product; (2) While having excellent magnetic properties, the magnetic powder has a good particle size distribution and particle morphology, so that the composite material can still have good fluidity and mechanical strength under the condition of high ferrite magnetic powder filling ratio.

[0004] When the average particle size of magnetic powder is large (small specific surface area), it is beneficial to improve the fluidity and mechanical strength of the injected ferrite composite material, but too coarse particle size of magnetic powder will lead to a significant decrease in the coercive force of magnetic powder. Therefore, seeking a ferrite magnetic powder with coarse particle size and good particle morphology (to ensure better fluidity) and better magnetic properties is an optional research direction.

[0005] The performance of ferrite powder can be improved by La-Co ion doping, and after La-Co ion doping, the magnetic powder can still have a high coercive force even if the particle size remains coarse. However, since La-Co ion doping needs to be carried out at a sufficiently high temperature (above 1200°C), the high temperature will cause the ferrite grains to grow flat, and the magnetic powder particles will eventually become flat. This flattened magnetic powder is not conducive to obtaining high fluidity when used in injection ferrite composite materials.

[0006] CN113889309A discloses a bonded ferrite magnetic powder for injection molding and its preparation method and application. The bonded ferrite magnetic powder for injection molding is prepared by adding fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns into a ball mill for ball milling, according to a weight ratio of the fine-grained ferrite magnetic powder accounting for 10 to 35 wt%, thereby obtaining a coarse and fine mixed magnetic powder. The bonded ferrite magnetic powder for injection molding can be mixed with a rubber binder, a plasticizer, and a stabilizer to prepare an injection-molded flexible bonded magnet.

[0007] CN118335508A discloses a process for preparing injection-molded ferrite and an injection-molded ferrite magnet. The process for preparing injection-molded ferrite comprises the following preparation steps: iron scale powder: 20-40 parts; strontium carbonate powder: 10-60 parts; water: 23-53 parts; red iron oxide: 10-40 parts; barium carbonate: 3-11 parts; silane coupling agent: 1-7 parts; dispersant: 1-6 parts; nylon-6: 10-20 parts; toughening and reinforcing agent: 1-7 parts; defoaming agent: 1-7 parts; lubricant: 1-9 parts; S1. preparing ferrite magnetic powder: a: uniformly mixing iron scale powder and strontium carbonate powder to obtain an added mixture; b: forming a ball with the mixture in a and water, wherein the ratio of water to the mixture is 1.6:1, and then pre-burning to obtain a clinker pre-burned material.

[0008] The injection ferrite materials disclosed in the prior art have certain defects, and there is a problem that it is impossible to have a coarser particle size, good particle morphology and better magnetic properties at the same time, so as to ensure that the injection ferrite material has better fluidity and magnetic properties at the same time. Therefore, it is very important to develop and design a new type of injection ferrite magnetic powder and preparation method, injection ferrite material and application. Summary of the invention

[0009] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide an injection ferrite magnetic powder and a preparation method thereof, an injection ferrite material and an application. The injection ferrite magnetic powder provided in the present invention not only has a relatively coarse particle size, but also has a good particle morphology because the average aspect ratio L / D is 1.2 to 3.0. Therefore, the injection ferrite magnetic powder has better fluidity. In addition, due to the doping of La and Co, the injection ferrite magnetic powder also has excellent magnetic properties.

[0010] To achieve this purpose, the present invention adopts the following technical solutions:

[0011] In the first aspect, the present invention provides an injection ferrite magnetic powder, and the chemical formula of the injection ferrite magnetic powder is Sr 1-x-y La x Ca y Fe 12-z Co z O 19 , the D50 size is 1.5 to 2.5 μm, and the average aspect ratio L / D is 1.2 to 3.0;

[0012] Among them, 0 < x ≤ 0.4, 0 < y ≤ 0.4, 0 < z ≤ 0.25, 1.3 ≤ x / z ≤ 1.6.

[0013] In the present invention, the D50 size of the injection ferrite magnetic powder is 1.5 to 2.5 μm. For example, it can be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm or 2.5 μm, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0014] In the present invention, the average aspect ratio L / D of the injection ferrite magnetic powder is 1.2 to 3.0. For example, it can be 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8 or 3.0, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0015] In the present invention, 0 < x ≤ 0.4, and the value of x can be, for example, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0016] In the present invention, 0 < y ≤ 0.4, and the value of y can be, for example, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0017] In the present invention, 0 < z ≤ 0.25. The value of z can be, for example, 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22 or 0.25, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0018] In the present invention, 1.3 ≤ x / z ≤ 1.6. The value of x / z can be, for example, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0019] The injection ferrite magnetic powder provided in the present invention not only has a relatively coarse particle size, but also has a good particle morphology due to the aspect ratio L / D ranging from 1.2 to 3.0. Therefore, the injection ferrite magnetic powder has relatively excellent fluidity. In addition, due to the doping of La and Co, the injection ferrite magnetic powder also has excellent magnetic properties.

[0020] Preferably, the D50 size of the injection ferrite magnetic powder is 1.5 - 2.0 μm, the proportion of particles with sizes between 1 μm and 5 μm is greater than 90%, the proportion of magnetic powder particles with sizes less than 1 μm is less than 5%, and the proportion of magnetic powder particles with sizes greater than 5 μm is less than 5%.

[0021] In the present invention, the D50 size of the injection ferrite magnetic powder is 1.5 - 2.0 μm. It can be, for example, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2.0 μm, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0022] In the present invention, the proportion of the injection ferrite magnetic powder with sizes between 1 μm and 5 μm is greater than 90%. It can be, for example, 90.1%, 90.5%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0023] In the present invention, the proportion of magnetic powder particles of the injection ferrite magnetic powder with sizes less than 1 μm is less than 5%. It can be, for example, 4.9%, 4.8%, 4.5%, 4.3%, 4.0%, 3.5%, 3%, 2.5%, 2.0%, 1.5%, 1.0%, 0.5% or 0.1%, but is not limited to the listed values. Other unlisted values within this numerical range are equally applicable.

[0024] The proportion of magnetic powder particles with a size greater than 5 μm in the injected ferrite magnetic powder described in the present invention is less than 5%, for example, it can be 4.9%, 4.8%, 4.5%, 4.3%, 4.0%, 3.5%, 3%, 2.5%, 2.0%, 1.5%, 1.0%, 0.5% or 0.1%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In a second aspect, the present invention provides a method for preparing the injected ferrite magnetic powder according to the first aspect, the preparation method comprising:

[0026] Mixing Sr source, La source, Ca source, Fe source, Co source, H3BO3 and SrCl2 to obtain mixed powder, and then calcining and crushing the obtained mixed powder in sequence to obtain the injection ferrite magnetic powder;

[0027] Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1-1.5wt%, the mass fraction of SrCl2 is 1-2wt%, and the mass ratio of H3BO3 to SrCl2 is 0.75-1.

[0028] In the present invention, the mass fraction of H3BO3 in the mixed powder is 1-1.5wt%, for example, it can be 1wt%, 1.05wt%, 1.1wt%, 1.15wt%, 1.2wt%, 1.25wt%, 1.3wt%, 1.35wt%, 1.4wt%, 1.45wt% or 1.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In the present invention, the mass fraction of SrCl2 in the mixed powder is 1-2wt%, for example, it can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In the present invention, the mass ratio of H3BO3 to SrCl2 is 0.75-1, for example, it can be 0.75, 0.78, 0.80, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95, 0.98 or 1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the mixing method includes a first ball milling, and the time of the first ball milling is 1 to 5 hours, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, water is added during the first ball milling process, and the first ball milling is followed by drying to obtain a mixed powder.

[0033] Preferably, the drying temperature after the first ball milling is 90-130°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the Sr source comprises SrCO3.

[0035] Preferably, the La source includes La2O3.

[0036] Preferably, the Ca source comprises CaCO3.

[0037] Preferably, the Fe source comprises Fe2O3.

[0038] Preferably, the Co source comprises Co2O3.

[0039] Preferably, the calcination temperature is 1200-1300° C. and the calcination time is 1-3 hours.

[0040] The calcination temperature in the present invention is 1200-1300°C, for example, it can be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C or 1300°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The calcination time in the present invention is 1 to 3 hours, for example, it can be 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the pulverizing comprises Raymond milling, second ball milling and vibration milling performed in sequence.

[0043] Preferably, the D50 particle size of the powder after Raymond milling is less than 10 μm, for example, it can be 10 μm, 9 μm, 8 μm, 7 μm, 6 μm, 5 μm, 4 μm, 3 μm, 2 μm or 1 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the second ball milling time is 10 to 15 h, for example, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h or 15 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, water is added during the second ball milling process, and the second ball milling is followed by drying to obtain a powder after the second ball milling.

[0046] Preferably, the temperature of the second drying after ball milling is 90-130°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the D50 particle size of the powder obtained after the second ball milling is 2.0 to 2.5 μm, for example, it can be 2.0 μm, 2.05 μm, 2.1 μm, 2.15 μm, 2.2 μm, 2.25 μm, 2.3 μm, 2.35 μm, 2.4 μm, 2.45 μm or 2.5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the D50 particle size of the powder obtained after the vibration milling is 1.5 to 2.0 μm, for example, it can be 1.5 μm, 1.55 μm, 1.6 μm, 1.65 μm, 1.7 μm, 1.75 μm, 1.8 μm, 1.85 μm, 1.9 μm, 1.95 μm or 2.0 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the pulverization further includes heat treatment and deagglomeration performed in sequence.

[0050] Preferably, the pulverizing and heat treatment further includes mixing Bi2O3 with the pulverized powder.

[0051] Preferably, the mass ratio of Bi2O3 to the crushed powder is (0.1-1):100, for example, it can be 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100 or 1:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the heat treatment is performed at a temperature of 700 to 1100° C. and for a time of 0.1 to 3.0 h.

[0053] The temperature of the heat treatment in the present invention is 700-1100°C, for example, it can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] The heat treatment time in the present invention is 0.1 to 3.0 h, for example, it can be 0.1 h, 0.3 h, 0.5 h, 0.7 h, 1 h, 1.2 h, 1.5 h, 1.7 h, 2.0 h, 2.2 h, 2.5 h, 2.7 h or 3.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the deagglomeration comprises ball milling the heat-treated powder using a sand mill with lightweight balls.

[0056] Preferably, the density of the lightweight ball is 1.5-2.0 g / cm 3 , for example, it can be 1.5 g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the diameter of the lightweight ball is 1 to 3 mm, for example, it can be 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm or 3 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] The lightweight ball in the present invention may be, for example, an iron core nylon ball (with a diameter of 8 mm and a surface nylon thickness of 2 mm).

[0059] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:

[0060] (1) mixing a Sr source, a La source, a Ca source, a Fe source, a Co source, H3BO3 and SrCl2 by first ball milling for 1 to 5 hours, adding water during the first ball milling, and drying at 90 to 130° C. after the first ball milling to obtain a mixed powder;

[0061] Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1-1.5wt%, the mass fraction of SrCl2 is 1-2wt%, and the mass ratio of H3BO3 to SrCl2 is 0.75-1;

[0062] (2) calcining the mixed powder obtained in step (1) at 1200-1300° C. for 1-3 h, and then subjecting the powder to a Raymond mill so that the D50 particle size of the powder is less than 10 μm; then subjecting the powder to a second ball milling for 10-15 h, adding water during the second ball milling, and drying the powder at 90-130° C. after the second ball milling to obtain a powder having a D50 particle size of 2.0-2.5 μm; and then subjecting the powder to a vibration mill to obtain a powder having a D50 particle size of 1.5-2.0 μm;

[0063] (3) Mixing Bi2O3 in a mass ratio of (0.1-1):100 with the powder having a D50 particle size of 1.5-2.0 μm obtained in step (2), heat treating the mixture at 700-1100° C. for 0.1-3.0 h, and then milling the heat treated powder with a sand mill using lightweight balls to obtain the injected ferrite magnetic powder.

[0064] In a third aspect, the present invention provides an injected ferrite material, wherein the injected ferrite material comprises the injected ferrite magnetic powder described in the first aspect.

[0065] In a fourth aspect, the present invention provides an application of the injected ferrite material described in the third aspect, wherein the injected ferrite material is used in the fields of motors, magnetic storage, magnetic adsorption and magnetic sensing.

[0066] Compared with the prior art, the present invention has the following beneficial effects:

[0067] (1) The injected ferrite magnetic powder provided in the present invention not only has a coarser particle size, but also has a good particle morphology due to the average aspect ratio L / D of 1.2 to 3.0, so the injected ferrite magnetic powder has better fluidity; in addition, due to the doping of La and Co, the injected ferrite magnetic powder also has excellent magnetic properties;

[0068] (2) In the preparation method of the injected ferrite magnetic powder provided by the present invention, the addition of H3BO3 and SrCl2 plays a fluxing effect. The low melting points of H3BO3 and SrCl2 are used to promote the mutual diffusion of La and Co ions and Sr, Fe, and Ca ions, so that Sr can be formed at a relatively low temperature. 1-x-y La x Ca y Fe 12-z Co z O 19 On the other hand, since H3BO3 can promote the axial growth of ferrite grains, and SrCl2 can promote the radial growth of ferrite particles, by controlling the ratio of H3BO3 to SrCl2, the particle size of ferrite particles and the aspect ratio L / D of the particles can be controlled, thereby obtaining injected ferrite powder with coarser particle size, good particle morphology and excellent magnetic properties. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] Example 1

[0071] This embodiment provides an injection ferrite magnetic powder, the chemical formula of the injection ferrite magnetic powder is Sr 1-x- y La x Ca y Fe 12-z Co z O 19 , the average aspect ratio L / D is 2.35;

[0072] Among them, x=0.4, y=0.4, z=0.25, x / z=1.6.

[0073] The D50 size of the injected ferrite magnetic powder is 1.90 μm, the proportion of magnetic powder particles with a size between 1 μm and 5 μm is greater than 90%, the proportion of magnetic powder particles with a size less than 1 μm is less than 5%, and the proportion of magnetic powder particles with a size greater than 5 μm is less than 5%.

[0074] The preparation method of the injected ferrite powder is:

[0075] (1) SrCO3, La2O3, CaCO3, Fe2O3, Co2O3, H3BO3 and SrCl2 were mixed by first ball milling for 3 hours, water was added during the first ball milling, and the mixture was dried at 110° C. after the first ball milling to obtain a mixed powder;

[0076] Based on the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1.5wt%, the mass fraction of SrCl2 is 2wt%, and the mass ratio of H3BO3 to SrCl2 is 0.75;

[0077] (2) calcining the mixed powder obtained in step (1) at 1200° C. for 2 h, and then subjecting the powder to a Raymond mill so that the D50 particle size of the powder is less than 10 μm; then subjecting the powder to a second ball milling for 15 h, adding water during the second ball milling, and drying the powder at 110° C. after the second ball milling to obtain a powder with a D50 particle size of 2.45 μm; and then subjecting the powder to a vibration mill to obtain a powder with a D50 particle size of 1.85 μm;

[0078] (3) After mixing Bi2O3 with a mass ratio of 0.5:100 and the powder with a D50 particle size of 1.85 μm obtained in step (2), the mixture is heat treated at 900° C. for 2.0 h, and then the heat-treated powder is milled with a sand mill using lightweight balls to deagglomerate the powder, thereby obtaining the injected ferrite magnetic powder.

[0079] Example 2

[0080] This embodiment provides an injection ferrite magnetic powder, the chemical formula of the injection ferrite magnetic powder is Sr 1-x- y La x Ca y Fe 12-z Co z O 19 , the average aspect ratio L / D is 1.2;

[0081] Among them, x=0.1, y=0.4, z=0.077, x / z=1.3.

[0082] The D50 size of the injected ferrite magnetic powder is 1.5 μm, the proportion of particles with a size between 1 μm and 5 μm is greater than 90%, the proportion of particles with a size less than 1 μm is less than 5%, and the proportion of particles with a size greater than 5 μm is less than 5%.

[0083] The preparation method of the injected ferrite powder is:

[0084] (1) SrCO3, La2O3, CaCO3, Fe2O3, Co2O3, H3BO3 and SrCl2 were mixed by first ball milling for 5 hours, water was added during the first ball milling, and the mixture was dried at 90° C. after the first ball milling to obtain a mixed powder;

[0085] Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1.5wt%, the mass fraction of SrCl2 is 1.5wt%, and the mass ratio of H3BO3 to SrCl2 is 1;

[0086] (2) calcining the mixed powder obtained in step (1) at 1300° C. for 1 h, and then subjecting the powder to a Raymond mill so that the D50 particle size of the powder is less than 10 μm; then subjecting the powder to a second ball milling for 15 h, adding water during the second ball milling, and drying the powder at 90° C. after the second ball milling to obtain a powder with a D50 particle size of 2.0 μm; and then subjecting the powder to a vibration mill to obtain a powder with a D50 particle size of 1.5 μm;

[0087] (3) After mixing Bi2O3 with a mass ratio of 0.1:100 and the powder with a D50 particle size of 1.5 μm obtained in step (2), the mixture is heat treated at 1100° C. for 0.1 h, and then the heat-treated powder is milled with a sand mill using lightweight balls to deagglomerate the powder, thereby obtaining the injected ferrite magnetic powder.

[0088] Example 3

[0089] This embodiment provides an injection ferrite magnetic powder, the chemical formula of the injection ferrite magnetic powder is Sr 1-x- y La x Ca y Fe 12-z Co z O 19 , the average aspect ratio L / D is 3.0;

[0090] Among them, x=0.4, y=0.1, z=0.25, x / z≤1.6.

[0091] The D50 size of the injected ferrite magnetic powder is 2.0 μm, the proportion of particles with a size between 1 μm and 5 μm is greater than 90%, the proportion of particles with a size less than 1 μm is less than 5%, and the proportion of particles with a size greater than 5 μm is less than 5%.

[0092] The preparation method of the injected ferrite powder is:

[0093] (1) SrCO3, La2O3, CaCO3, Fe2O3, Co2O3, H3BO3 and SrCl2 were mixed by first ball milling for 1 h, water was added during the first ball milling, and the mixture was dried at 130° C. after the first ball milling to obtain a mixed powder;

[0094] Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1wt%, the mass fraction of SrCl2 is 1.25wt%, and the mass ratio of H3BO3 to SrCl2 is 0.8;

[0095] (2) calcining the mixed powder obtained in step (1) at 1200° C. for 3 h, and then subjecting the powder to a Raymond mill so that the D50 particle size of the powder is less than 10 μm; then subjecting the powder to a second ball milling for 10 h, adding water during the second ball milling, and drying the powder at 130° C. after the second ball milling to obtain a powder with a D50 particle size of 2.5 μm; and then subjecting the powder to a vibration mill to obtain a powder with a D50 particle size of 2.0 μm;

[0096] (3) After mixing Bi2O3 with a mass ratio of 1:100 and the powder with a D50 particle size of 2.0 μm obtained in step (2), heat treatment is performed at 700°C for 3.0 h, and then the heat-treated powder is subjected to ball milling deagglomeration treatment using a sand mill with lightweight balls to obtain the injected ferrite magnetic powder.

[0097] Example 4

[0098] The present embodiment provides an injected ferrite magnetic powder, which is the same as the embodiment 1 except that the D50 size of the injected ferrite magnetic powder is 2.13 μm, the average aspect ratio L / D is 2.55, that is, in step (2) of the preparation method of the injected ferrite magnetic powder, the powder with a D50 particle size of 1.95 μm is obtained by vibration grinding.

[0099] Example 5

[0100] This embodiment provides an injected ferrite magnetic powder, which is the same as Embodiment 1 except that the D50 size of the injected ferrite magnetic powder is 1.5 μm and the average aspect ratio L / D is 1.8, i.e. the vibration grinding in step (2) of the preparation method of the injected ferrite magnetic powder is omitted.

[0101] Example 6

[0102] The present embodiment provides an injected ferrite magnetic powder, which is the same as that of Embodiment 1 except that the D50 size of the injected ferrite magnetic powder is 2.5 μm, the average aspect ratio L / D is 3.0, that is, the mass ratio of Bi2O3 to the powder obtained in step (2) during mixing in step (3) of the preparation method of the injected ferrite magnetic powder is 0.01:100.

[0103] Example 7

[0104] The present embodiment provides an injected ferrite magnetic powder, which is the same as that of Embodiment 1 except that the D50 size of the injected ferrite magnetic powder is 1.8 μm, the average aspect ratio L / D is 1.3, that is, the mass ratio of Bi2O3 to the powder obtained in step (2) during mixing in step (3) of the preparation method of the injected ferrite magnetic powder is 2:100.

[0105] Example 8

[0106] This embodiment provides an injected ferrite magnetic powder, which is the same as Embodiment 1 except that the D50 size of the injected ferrite magnetic powder is 1.6 μm, the average aspect ratio L / D is 2.3, and the calcination temperature in step (2) of the preparation method of the injected ferrite magnetic powder is 1350°C.

[0107] Comparative Example 1

[0108] This comparative example provides an injected ferrite magnetic powder, which is the same as Example 1 except that z=0, the D50 size of the injected ferrite magnetic powder is 2.3.μm, and the average aspect ratio L / D is 3.1.

[0109] Comparative Example 2

[0110] This comparative example provides an injected ferrite magnetic powder, which is the same as Example 1 except that z=0.3, the D50 size of the injected ferrite magnetic powder is 1.92 μm, and the average aspect ratio L / D is 2.33.

[0111] Comparative Example 3

[0112] This comparative example provides an injected ferrite magnetic powder, except that x=0.3, y=0.3, z=0.3, the D50 size of the injected ferrite magnetic powder is 3.0μm, and the average aspect ratio L / D is 1.0. That is, in step (1) of the preparation method of the injected ferrite magnetic powder, based on the mass of the mixed powder, the mass fraction of H3BO3 in the mixed powder is 0.5wt% and the mass fraction of SrCl2 is 0.5wt%, and the mass ratio of H3BO3 to SrCl2 is 1:1, and the rest is the same as Example 1.

[0113] Comparative Example 4

[0114] This comparative example provides an injected ferrite magnetic powder, except that x=0.1, y=0.1, z=0.05, the D50 size of the injected ferrite magnetic powder is 3.5μm, and the average aspect ratio L / D is 3.3. That is, in step (1) of the preparation method of the injected ferrite magnetic powder, based on the mass of the mixed powder, the mass fraction of H3BO3 in the mixed powder is 0.5wt% and the mass fraction of SrCl2 is 3.0wt%, and the mass ratio of H3BO3 to SrCl2 is 1:6, and the rest is the same as Example 1.

[0115] The particle size of the injected ferrite magnetic powder provided in the above embodiment and comparative example was tested by using a laser particle size analyzer, and the D50 particle size of the injected ferrite magnetic powder in the above embodiment and comparative example was as shown in the above embodiment and comparative example;

[0116] The magnetic properties of the injected ferrite powder provided in the above embodiments and comparative examples were tested using a vibrating sample magnetometer (VSM), and the saturation magnetization (Ms), residual magnetization (Mr) and intrinsic coercive force (Hcj) of the injected ferrite powder were obtained as shown in Table 1.

[0117] Table 1

[0118]

[0119]

[0120] From Table 1, we can get:

[0121] (1) The injected ferrite powders provided in Examples 1 to 4 have higher saturation magnetization, higher residual magnetization and higher intrinsic coercivity, and exhibit better fluidity;

[0122] (2) By comparing Example 1 with Example 5, it can be seen that the vibration grinding in the preparation method of the injected ferrite magnetic powder is beneficial to improving the performance of the injected ferrite magnetic powder. This is because when the magnetic powder obtained by ball milling breaks, corners and sharp protrusions will be generated. This organizational morphology is not conducive to the high fluidity of the magnetic powder. Moreover, after the magnetic powder of this form is mixed and granulated with engineering plastics, the strength and magnetic properties of the material are relatively low. Therefore, in the present invention, a vibration grinding step is added. Through relatively low-energy vibration grinding, these corners and protrusions are reduced or eliminated, thereby improving the fluidity of the magnetic powder.

[0123] (3) By comparing Example 1 with Examples 6 and 7, it can be seen that mixing a suitable mass fraction of Bi2O3 in step (3) of the method for preparing the injected ferrite magnetic powder is beneficial to improving the performance of the injected ferrite magnetic powder. This is because after adding Bi2O3, the fluxing effect of Bi2O3 is utilized to make it easier for the powder to eliminate the deformation stress generated during the ball milling and vibration milling process during the annealing process, repair the powder lattice defects, and thus improve the magnetic properties of the injected ferrite magnetic powder.

[0124] (4) By comparing Example 1 with Example 8, it can be seen that the calcination temperature in step (2) of the method for preparing the injected ferrite magnetic powder of the present invention affects the performance of the injected ferrite magnetic powder. When the calcination temperature is 1200-1300°C, it is conducive to obtaining injected ferrite magnetic powder with better performance. This is because the Co ions in the magnetic powder calcined within this temperature range diffuse more fully, the grains are not too coarse, and the aspect ratio of the magnetic powder particles is maintained in a relatively suitable range.

[0125] (5) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the addition of a suitable amount of Co in the present invention is beneficial to improving the performance of the injected ferrite powder. This is because the addition of Co ions increases the saturation magnetization intensity and anisotropy field of the magnetic powder, thereby improving the intrinsic magnetic properties of the magnetic powder.

[0126] (6) By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the injected ferrite magnetic powder provided in the present invention not only has a coarser particle size, but also has a good particle morphology due to the aspect ratio L / D ranging from 1.2 to 3.0, so the injected ferrite magnetic powder has excellent fluidity; in addition, due to the doping of La and Co, the injected ferrite magnetic powder also has excellent magnetic properties; in the preparation method of the injected ferrite magnetic powder provided by the present invention, the addition of H3BO3 and SrCl2 plays a fluxing effect on the one hand, and utilizes the low melting point of H3BO3 and SrCl2 to promote the mutual diffusion of La, Co ions and Sr, Fe, Ca ions, so that Sr can be formed at a lower temperature. 1-x-y La x Ca y Fe 12-z Co z O 19 On the other hand, since H3BO3 can promote the axial growth of ferrite grains, and SrCl2 can promote the radial growth of ferrite particles, by controlling the ratio of H3BO3 to SrCl2, the particle size of ferrite particles and the aspect ratio L / D of the particles can be controlled, thereby obtaining injected ferrite powder with coarser particle size, good particle morphology and excellent magnetic properties.

[0127] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An injected ferrite powder, characterized in that: The chemical formula of the injected ferrite powder is Sr 1-x- y La x Ca y Fe 12-z Co z O 19 , D50 size is 1.5-2.5 μm, and the average aspect ratio L / D is 1.2-3.0; Among them, 0 <x≤0.4,0<y≤0.4,0<z≤0.25,1.3≤x / z≤1.6。 2. The injected ferrite powder according to claim 1, characterized in that: The D50 size of the injected ferrite magnetic powder is 1.5-2.0 μm, the proportion of particles with a size between 1 μm and 5 μm is greater than 90%, the proportion of particles with a size less than 1 μm is less than 5%, and the proportion of particles with a size greater than 5 μm is less than 5%.

3. A method for preparing the injected ferrite powder according to claim 1 or 2, characterized in that: The preparation method comprises: Mixing Sr source, La source, Ca source, Fe source, Co source, H3BO3 and SrCl2 to obtain mixed powder, and then calcining and crushing the obtained mixed powder in sequence to obtain the injection ferrite magnetic powder; Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1-1.5wt%, the mass fraction of SrCl2 is 1-2wt%, and the mass ratio of H3BO3 to SrCl2 is 0.75-1.

4. The preparation method according to claim 3, characterized in that: The mixing method includes a first ball milling, wherein the time of the first ball milling is 1 to 5 hours; Preferably, the Sr source comprises SrCO3; Preferably, the La source comprises La2O3; Preferably, the Ca source comprises CaCO3; Preferably, the Fe source comprises Fe2O3; Preferably, the Co source comprises Co2O3.

5. The preparation method according to claim 3 or 4, characterized in that: The calcination temperature is 1200-1300° C. and the calcination time is 1-3 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The pulverization includes Raymond milling, second ball milling and vibration milling in sequence; Preferably, the D50 particle size of the powder after Raymond milling is less than 10 μm; Preferably, the D50 particle size of the powder obtained after the second ball milling is 2.0 to 2.5 μm; Preferably, the powder obtained after the vibration milling has a D50 particle size of 1.5 to 2.0 μm.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The pulverization further includes heat treatment and deagglomeration in sequence; Preferably, the pulverization and heat treatment further include mixing Bi2O3 with the pulverized powder; Preferably, the mass ratio of Bi2O3 to the crushed powder is (0.1-1):100; Preferably, the heat treatment temperature is 700-1100°C and the time is 0.1-3.0h; Preferably, the deagglomeration comprises ball milling the heat-treated powder using a sand mill with lightweight balls.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The preparation method comprises: (1) mixing a Sr source, a La source, a Ca source, a Fe source, a Co source, H3BO3 and SrCl2 by first ball milling for 1 to 5 hours, adding water during the first ball milling, and drying at 90 to 130° C. after the first ball milling to obtain a mixed powder; Taking the mass of the mixed powder as 100%, the mass fraction of H3BO3 in the mixed powder is 1-1.5wt%, the mass fraction of SrCl2 is 1-2wt%, and the mass ratio of H3BO3 to SrCl2 is 0.75-1; (2) calcining the mixed powder obtained in step (1) at 1200-1300° C. for 1-3 h, and then subjecting the powder to a Raymond mill so that the D50 particle size of the powder is less than 10 μm; then subjecting the powder to a second ball milling for 10-15 h, adding water during the second ball milling, and drying the powder at 90-130° C. after the second ball milling to obtain a powder having a D50 particle size of 2.0-2.5 μm; and then subjecting the powder to a vibration mill to obtain a powder having a D50 particle size of 1.5-2.0 μm; (3) Mixing Bi2O3 in a mass ratio of (0.1-1):100 with the powder having a D50 particle size of 1.5-2.0 μm obtained in step (2), heat treating the mixture at 700-1100° C. for 0.1-3.0 h, and then milling the heat treated powder with a sand mill using lightweight balls to obtain the injected ferrite magnetic powder.

9. An injection ferrite material, characterized in that: The injected ferrite material comprises the injected ferrite magnetic powder according to claim 1 or 2.

10. An application of the injection ferrite material according to claim 9, characterized in that: The injected ferrite material is used in the fields of motors, magnetic storage, magnetic adsorption and magnetic sensing.

Citation Information

Patent Citations

  • Bonded ferrite magnetic powder for injection molding as well as preparation method and application of bonded ferrite magnetic powder

    CN113889309A

  • Injection molding ferrite preparation process and injection molding ferrite magnet

    CN118335508A

  • High-performance permanent magnetic ferrite and manufacturing method thereof

    CN104261811A

  • Permanent magnetic ferrite material for automobile starting motor

    CN116477935A

  • Ferrite powder for bond magnet and method for manufacturing the same

    JP2020038963A